Pemanfaatan e-commerce dan m-commerce dalam bisnis di kalangan wirausahawan perempuan - Ika Yunia Fauzia (Journal of Business & Banking, 2015)
This study discusses the use of e-commerce and m-commerce by female entrepreneurs, the majority was housewives. This study uses a qualitative method for exposing a phe-nomenon and the behavior that occurs. It uses descriptive design which allows for the study of profound and piercing the target. Thus, this research modle is the linear snowball to get 100 female entrepreneurs who do business with e-commerce and m-commerce. The findings show that some female entrepreneurs take advantage of e-commerce for retail sales, wholesalers, agents and distributors of a product / service and also in some remote areas, e-commerce, they can help some entrepreneurs to jump-start their business in a way to explore e-commerce for looking for a supplier. Utiliza-tion of e-commerce is relatively easier for the beginner entrepreneurs in the condition of contacts through mobile that is a demand for the products they offer. It suggests that further study can be done discussing the similar e-commerce which aims to support the emergence of women entrepreneurs as a reinforcement of the household finances with-out abandoning their responsibilities as a mother